New insights into the formation of fayalitic olivine from Allende dark inclusions - Varela, Maria Eugenia (2012)
Although considerable progress has been made in unraveling the origin(s) of fayalitic olivines in dark inclusions (DIs), many questions remain still unresolved and/or controversial. We combine a chemical and petrographic study of the Allende dark inclusion 4884-2B (AMNH, New York) and ATEM studies of a fragment of the dark inclusion Allende AF (NHM, Vienna) and discuss an alternative way in which fayalitic olivines could have formed. Allende dark inclusion 4884-2B contains a few aggregates with variable proportions of transparent and feathery olivine. Two such objects (aggregates A and B) are the focus of this study as they preserve glasses that can help in deciphering the nature of the processes involved during olivine growth and subsequent olivine transformation. The petrographic and chemical characteristics of aggregates A and B indicate that the forsteritic stack olivines may be pseudomorphs of clear olivine crystals. The ATEM studies in All-AF suggest that fayalitic olivines may be the result of secondary processes (e.g., metasomatic exchange reactions) operating in the solar nebula. Transformation may have occurred through the mediation of a dry gas phase involving nonvolatile major elements, such as Mg and Fe (e.g., Dohmen et al. 1998). This mechanism could reveal olivine growth patterns (e.g., stacked platelets due to a rapid growth regime) and may have contributed to the development of their fibrous aspect while preserving the shape (i.e., volume) of the crystals. This highly selective process did completely or partially transform ferromagnesian minerals, but affected the fine-grained mesostasis only slightly.